Effect of COVID-19 on Severity of Signs and Symptoms of Autoimmune Diseases - Haji, Ramand Mohammed; Ahmed, Nabaz Ali; Ahmed, Shakhawan Azad (Kurdistan Journal of Applied Research, 2022)
It is an observational cross-sectional study, the data collected by convenience sampling method from 33 patients in the Ranya General Hospital and private clinics for follow-up patient’s autoimmune diseases state in the Ranya city from the 10th November 2020 to the 20th May 2021 and the study included all the patients had autoimmune diseases that recovered from the COVID-19 disease. For the study materials, the data was collected by a questionnaire form that included demographic and autoimmune disease questions also questions about the patient’s intensity of their autoimmune disease’s signs and symptoms before and after they recovered from COVID-19. Determine patient’s autoimmune disease signs and symptoms intensity based on the prescribed drug for a treat the autoimmune diseases which are changed by special doctors. Furthermore, the data were analysed by SPSS software to produce descriptive statistic measures and to find the difference between dependent categorical variables Sign tests were used but the Chi-square test was used for the categorical independent variables with regarding 0.05 as a significant critical value. The result reveals that the range of their age started from 42 to 74 years old with mean±standard deviation (57.3 ± 8.06) and most of the cases 15(45.5%) were between (55-65) years old, followed by less than 55 years old 13(39.4%) and more than 65 years old age 5(3.8%) cases respectively. Rheumatoid arthritis was a major type 16 (48.5%) of the autoimmune disease compared to other types, Ankylosing Spondylitis 8(24.2%) cases, and Ulcerative Colitis 6(18.2%) cases respectively while Crohn’s disease was the minimum 3(9.1%) cases and before the got COVID-19 most of the cases 25(75.8%) had moderate intensity signs and symptoms of their autoimmune diseases and 8(24.2%) cases had severe signs and symptoms but after they recovered from the COVID-19 disease the rate of their signs and symptoms changed to mild 19(57.6%) and moderate 14(42.4%) intensity while severe intensity signs and symptoms were zero with highly significant differences (P-value 0.0001). Despite the current study concluded autoimmune disease patients recovered from the COVID-19 their autoimmune diseases signs and symptoms intensity decreased significantly but still further studies are needed with a bigger sample size to determine and explain this association.